PENGEMBANGAN MEDIA PEMBELAJARAN TEKNIK DASAR BOLA VOLI UNTUK SISWA SEKOLAH MENENGAH PERTAMA - Putro, Danang Endarto (Dinamika, 2014)
195Â This study aims to produce learning media of volleyball basic technique for junior high scholl students. The study used research and development design. The prosedures were done as follow: (1) doing need analysis, (2) developing assessment instruments, (3) developing and selecting instructional materials, (4) designing and conducting formative evaluation of instruction, and (5) making final product. The small scale trial was conducted to 30 students of SMP N 1 Jetis, while the bigger scale trial was done to 57 students (28 students of SMP N 1 Bantul and 29 of SMP N 1 Imogiri). Product quality assessment involves 3 physical education teachers. The instruments which were used in collecting data were: (1) general interview instruction, (2) validation scale questionnaire, and (3) questionnaire of quality scale of the learning media. The research show that the validations; (1) from material expert is very good, (2) from media expert is very good, (3) from overall students is very good, (4) from teacher is very good.The effectiveness of learning media was 5.4 on pretest and 8.6 on posttest. Â Keywords: learning media, basic techniques volleyball.